Formal Translation On Indonesian President Speech - Pramitha, Asi Intan (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2015)
AbstractThis research analyzes President Speech Script from â€œState Address by President of the Republic of Indonesia on the Occasion of the 65th Anniversary of Independence of the Republic Indonesia which contains two languages. The purpose of this research is to discover the language expressions to know which the level of formality used in President Speech in translation of Indonesian into English. The writer analyzes the President speech as the unit of analysis. The method of this research is descriptive qualitative by comparing two text of President Speech, the Source Language (Indonesian) and Target Language (English). It uses the level of formality theory to analyze the language expressions used in translation of Indonesian into English. In this research the writer finds that there are some words, phrases, and sentences which those expressions show the formality. Based on this research, the formality mostly showed from the diction or word order and tone. Also, there are some expressions which are generally used by a President in his Speech. So, the result of translation is formal based on the analysis which has been done. —tentang pidato president Indonesia pada kegiatan peringatan hari kemerdekaan bangsa Indonesia yang ke-65 tahun. Penelitian ini bertujuan untuk mengetahui tingkat formalitas penerjemahan ungkapan bahasa yang digunakan oleh president Indonesia dalam menyampaikan pidatonya dalam bahasa Indonesia yang kemudian diterjemahan ke dalam bahasa Inggris. Penelitian ini menggunakan metode kualitatif deskriptif dengan membandingkan dua teks naskah pidato, bahasa Indonesia dan hasil terjemahannya dalam bahasa Inggris. Dalam melakukan penelitian ini, peneliti menggunakan teori formalitas berdasarkan sumber acuan buku teori penerjemahan. Penelitian ini, menympulkan bahwa hasil penerjemahan teks naskah pidato dari bahasa Indonesia ke dalam bahasa Inggris banyak menggunakan ungkapan-ungkapan bahasa formal. Hasil dari penelitian ini diharapkan dapat memberikan kontribusi bagi para pembaca dan pemerhati penerjemahan.